Influence of groove type on welding-induced residual stress, deformation and width of sensitization region in a SUS304 steel butt welded joint. (August 2015) - Ye, Yanhong; Cai, Jianpeng; Jiang, Xiaohua; Dai, Deping; Deng, Dean
Highlights: An advanced computational approach for simulating multi-pass welding process was developed. The influence of groove shape on welding residual stress distribution was studied. The influence of groove shape on angular distortion was examined. Groove shape has significant influence on residual stress, deformation and sensitization zone. Abstract: To join a medium or thick plate weldment with a full penetration, a groove is usually prepared in the space between two sections of metal. Because weld metal needs to be deposited within the groove to form the joint, it is expected that different groove type will require different heat input, which may consequently have influence on welding residual stress and deformation. Generally, different groove corresponds to different bead layout, so it can be foreseen that the groove type has a significant effect on temperature history, shape and size of heat affected zone, and region of sensitization in certain alloys such as austenitic stainless steel. The influences of groove type on residual stress, angular distortion and width of sensitization region in a SUS304 butt-welded joint were investigated by means of numerical simulation and experiment. Based on ABAQUS code, a computational approach with considering thermo-mechanical coupling behaviors, moving heat source, strain hardening and annealing effect was developed to simulate temperature profile, stress field and deformation in multi-pass joint. Welding temperature cycles, residual stress distributions and deformations in V, K and X groove joints were calculated through using the proposed computational procedure. Meanwhile, experiments were carried out to obtain residual stress distributions and angular distortions. Through comparing the numerical results and the measured data, the effectiveness and accuracy of the developed computational approach were verified. The simulation results show that groove type has a significant influence on welding residual stress distribution, angular distortion and width of sensitization region.